Cortisol Awakening Response Is Linked to Disease Course and Progression in Multiple Sclerosis - Kern, Simone; Krause, Ivonne; Horntrich, Antje; Thomas, Katja; Aderhold, Julia; Ziemssen, Tjalf (PLOS ONE, 2013)
Objectives Dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis has frequently been reported in multiple sclerosis (MS). So far, HPA axis function in MS has predominantly been studied under pharmacological stimulation which is associated with a series of methodological caveats. Knowledge of circadian cortisol patterns and cortisol awakening response (CAR) is still limited. Methods A total of 77 MS patients (55 relapsing-remitting MS (RRMS)/22 secondary-progressive MS (SPMS)) as well as 34 healthy control (HC) subjects were enrolled. Diurnal cortisol release was assessed by repeated salivary cortisol sampling. Neurological disability was rated by the Kurtzke’s Expanded Disability Status Scale (EDSS). Depressive symptoms and perceived stress were assessed by self-report measures. Results RRMS but not SPMS patients differed in circadian cortisol release from HC subjects. Differences in cortisol release were restricted to CAR. Treated and treatment naïve RRMS patients did not differ in CAR. In a RRMS follow-up cohort (nine months follow-up), RRMS patients with EDSS progression (≥0.5) expressed a significantly greater CAR compared to HC subjects. RRMS patients with a stable EDSS did not differ from HC subjects. Neither depressive symptoms nor perceived stress ratings were associated with CAR in RRMS patients. In a step-wise regression analysis, EDSS at baseline and CAR were predictive of EDSS at follow-up (R2 = 67%) for RRMS patients. Conclusions Circadian cortisol release, in particular CAR, shows a course specific pattern with most pronounced release in RRMS. There is also some evidence for greater CAR in RRMS patients with EDSS progression. As a consequence, CAR might be of predictive value in terms of neurological disability in RRMS patients. The possible role of neuroendocrine-immune interactions in MS pathogenesis is further discussed.